Co-Induction of ULK-1 and AHSP mRNAs in Erythroid Precursor Cells Isolated From a Sirolimus-Treated β-Thalassemia Patient: A Case Report Study - Matteo Zurlo; Alessia Finotti; Alessia Finotti; Maria Rita Gamberini; Roberto Gambari; Roberto Gambari (British Journal of Biomedical Science, 2025)
IntroductionThe β-thalassemias are inherited genetic disorders affecting the hematopoietic system and caused by mutations of the adult β-globin gene, leading to low or absent production of adult hemoglobin. In addition, an excess of free α-globin is associated with ineffective erythropoiesis. In fact, the free α-globin molecules are prone to precipitate, causing toxicity to the erythroid cells, and interference with red cell maturation. In order to counteract the detrimental effects of the excess of α-globin, two pathways might be activated in β-thalassemia erythroid cells, i.e. Unc-51-like kinase 1 (Ulk-1)-mediated induction of autophagy and increased expression of the α-hemoglobin stabilizing protein (AHSP).Case PresentationThe studied case was a male transfusion dependent TM (Thalassemia Major) patient, aged 43 years, with a β039/β+IVSI-110 genotype (XmnI polymorphism: -/-), starting the first blood transfusion when he was 5 months old, and participating to the NCT03877809 (Sirthalaclin) clinical trial.MethodsExpression of AHSP and Ulk-genes in Erythroid precursor cells (ErPCs) was studied by Reverse transcription (RT)-qPCR and Western blotting ErPCs were isolated from the propositus after 90 and 180 days of treatment with sirolimus.Results and DiscussionThis study demonstrates for the first time that increase in the production of γ-globin2 mRNA and HbF in ErPCs from a patient with β-thalassemia treated with sirolimus might be associated with co-induction of Ulk-1 and AHSP genes.